Repair of Wire Feeder Gears in a 1300-Watt MIG Welding Machine Using Reverse Engineering Technology - Rabbika, Anes Inda; Nugraha, Muhamad Hanhan; Rusdja, Andy Permana; Malik, Mochamad Irlan (Universitas Muhammadiyah Jakarta, 2024)
Material failure is a common occurrence in components subjected to continuous loads, often due to fatigue. In the MIG 1300-watt welding machine, the wire feeder gear transmission process continuously distributes energy, leading to eventual material failure. This failure disrupts the transmission of rotation to the feeder shaft, causing the wire exiting the torch to slip. To address this issue, reverse engineering technology is applied using computer-aided design (CAD), finite element analysis (FEA) assisted by computer-aided engineering (CAE), and computer-aided manufacturing (CAM), culminating in the production of prototypes with 3D printing technology. This research aims to repair the wire feeder gears by leveraging reverse engineering technology, which includes redrawing the gears and implementing developmental modifications using CAD/CAM tools. These modifications are then analyzed through FEA with CAE assistance, and the final prototype is produced using an Anet A8 V2 3D printer with Poly Lactic Acid (PLA) material.